Laminated polyester film and its manufacturing method
By coating the resin layer of carbon nanotubes and inorganic particles on the polyester film, the problem of degradation of antistatic properties of the two-axis directional polyester film during processing is solved, ensuring that it still has good antistatic properties and transparency after the coronal discharge treatment, and is suitable for packaging materials for electronic components.
Patent Information
- Application Number
- JP2020203877
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-19
- Filing Date
- 2020-12-09
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-12-09
AI Technical Summary
In the prior art, the antistatic properties of the two-axis directional polyester film are easily damaged during processing, and the surface treatment will affect transparency and conductivity, resulting in safety hazards in electronic components when packaging and unpacking.
A resin layer containing carbon nanotubes and inorganic particles is coated on one side of the polyester film. Through specific proportions and process treatment, it ensures that the antistatic properties remain good after the coronal discharge treatment, and improves conductivity and transparency by controlling the content and structure of the carbon nanotubes and inorganic particles.
It achieves excellent antistatic properties after coronal discharge treatment, while maintaining high transparency and conductivity, avoiding electrostatic damage to electronic components during packaging and unpacking.
Smart Images

Figure 0007625837000001 
Figure 0007625837000002 
Figure 0007625837000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated polyester film and a method for producing the same. [Background technology]
[0002] Thermoplastic resin films, particularly biaxially oriented polyester films, have excellent properties such as mechanical properties, electrical properties, dimensional stability, transparency, and chemical resistance, and are therefore widely used in many applications such as magnetic recording materials and packaging materials.
[0003] However, since polyester is generally an insulating resin, biaxially oriented polyester films have the disadvantage that they do not have antistatic properties as they are. Antistatic properties are imparted with the aim of suppressing foreign matter defects caused by dust adhesion due to charging, and the bias of electric charge can be neutralized by imparting electrical conductivity to the surface or inner layer of an insulating material. Among the methods for imparting antistatic properties to polyester films, the method of providing a conductive coating layer on the surface of the polyester film makes it easy to impart electrical conductivity while making use of various stable properties of the film, and various methods have been studied for imparting antistatic properties.
[0004] For example, known methods include a method of applying a styrene sulfonic acid copolymer, which is an ion-conductive antistatic agent (Patent Document 1), a method of combining a polythiophene-based conductive agent, which is an electron-conductive antistatic agent, with an epoxy crosslinking agent to achieve both transparency and antistatic properties in the coating film (Patent Document 2), and a method of using carbon nanotubes as an antistatic agent (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 61-204240 [Patent Document 2] JP 2004-58648 A [Patent Document 3] Patent No. 4454426 [Patent Document 4] JP 2010-013135 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the antistatic method of Patent Document 1, which uses an ion-conductive antistatic agent, has problems in that the conductivity is insufficient and the performance is easily lost due to wear. Also, the techniques of Patent Documents 2 and 3 have problems such as the antistatic properties decreasing during corona discharge treatment described below, the antistatic components being colored and easily losing transparency, and furthermore, affecting the characteristics in terms of quality control.
[0007] By the way, examples of applications in which antistatic biaxially oriented polyester films are used include protective films and cover tapes for electronic components and OLED components. Here, the problems will be described using cover tapes for electronic components as an example. When peeling the cover tape from an electronic component, the electronic component may inadvertently pop out due to the peeling charge of the cover tape, resulting in the electronic component being scattered, or a discharge may occur between the charged tape and the electronic component, resulting in the electronic component being electrically destroyed. In general, when electronic components are packaged with the cover tape and carrier tape, the electronic components are inspected from the cover tape side, for example, to check whether different types are mixed in, whether the lead terminals of the IC chip are bent, or whether the filling direction is incorrect. In order to make these inspections easy, there is a strong demand for the transparency of the cover tape, and highly transparent transparent polyester films and transparent polyolefin films that have been antistatically processed have been used.
[0008] However, in the process of producing the cover tape, multiple layers such as primer and sealant are formed on the conductive polyester film substrate, and friction during the processing step reduces the antistatic properties. Furthermore, as in Patent Document 4, for example, surface treatment such as discharge treatment may be performed to increase the adhesion between the polyester film substrate and the sealant material, but it has become clear that this treatment reduces the antistatic properties in the technology cited in the above patented technology.
[0009] An object of the present invention is to provide a laminated polyester film which is excellent in antistatic properties and which can maintain the excellent antistatic properties even after discharge treatment, and a method for producing the same. [Means for solving the problem]
[0010] The laminated polyester film and the method for producing the same according to the present invention have the following configurations. (1) A laminated polyester film having a resin layer (X) on at least one surface of a polyester film, the resin layer (X) containing carbon nanotubes (a) and inorganic particles (b). (2) The laminated polyester film according to (1), wherein when the surface resistivity of the surface of the resin layer (X) is defined as P1 (Ω / □), the following formula 1 is satisfied: P1<1.0 9 (Formula 1) (3) The laminated polyester film according to (2), wherein when the surface resistivity of the resin layer (X) surface after subjecting the resin layer (X) surface to a corona discharge treatment under the following conditions is P2 (Ω / □), the following formula 2 is satisfied: P2 / P1≦100 (Formula 2) [Corona discharge treatment conditions] Corona discharge treatment was performed under the following conditions: output 100W, discharge gap with ceramic electrode 1mm, electrode movement speed 6m / min, and treatment number 5 times. (4) The laminated polyester film according to any one of (1) to (3), wherein the inorganic particles (b) are oxide particles containing at least one element selected from the group consisting of Si, Al, Ti, Zr, Se, and Fe. (5) The laminated polyester film according to any one of (1) to (4), wherein the content of the carbon nanotubes (a) in the resin layer (X) is 0.05% by weight or more and 5.0% by weight or less based on the entire resin layer (X). (6) The laminated polyester film according to any one of (1) to (5), wherein the content of the inorganic particles (b) in the resin layer (X) is 5.0% by weight or more based on the entire resin layer (X). (7) The laminated polyester film according to any one of (1) to (6), which is used for applications in which a discharge treatment is performed. (8) A method for producing a laminated polyester film according to any one of (1) to (7), comprising the steps of applying a coating composition (x) containing carbon nanotubes (a) and inorganic particles (b) to at least one surface of a polyester film before completion of crystal orientation, and then stretching the polyester film by a uniaxial or biaxial stretching method to complete the crystal orientation of the polyester film. Effect of the Invention
[0011] According to the present invention, the laminated polyester film of the present invention has excellent antistatic properties, and furthermore, the laminated polyester film of the present invention has excellent antistatic properties even after discharge treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The laminated polyester film of the present invention is a laminated polyester film having a resin layer (X) on at least one side of a polyester film, the resin layer (X) containing carbon nanotubes (a) (hereinafter referred to as CNTs (a)) and inorganic particles (b).
[0013] <Polyester film as base material> In the laminated polyester film of the present invention, a resin layer (X) is provided on at least one surface of a polyester film (substrate film) serving as a substrate.
[0014] In the present invention, the polyester constituting the polyester film as the substrate is a general term for polymers in which the ester bond formed by polycondensation of dicarboxylic acid and diol is the main bond in the main chain. Preferred polyesters include those in which at least one dicarboxylic acid selected from ethylene terephthalate, ethylene-2,6-naphthalate, butylene terephthalate, propylene terephthalate, and 1,4-cyclohexanedimethylene terephthalate is the main constituent resin. These constituent resins may be used alone or in combination of two or more.
[0015] The substrate film used in the laminated polyester film of the present invention may be a single-layer film or a laminated film of two or more layers. For example, a laminated film may be a composite film having an inner layer portion and a surface layer portion, in which the inner layer portion does not substantially contain particles, and only the surface layer portion is provided with a layer containing particles.
[0016] In addition, various additives such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, and crosslinking agents may be added to the polyester resin composition constituting the polyester film substrate to the extent that the properties are not deteriorated.
[0017] In addition, it is preferable to use a biaxially oriented polyester film as the polyester film that is the substrate of the present invention. Here, "biaxial orientation" refers to a film that shows a biaxially oriented pattern by wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5 times in each of the longitudinal and transverse directions of the sheet, and then subjecting it to heat treatment to complete the crystal orientation.
[0018] The layer thickness of the polyester film serving as the substrate of the present invention is appropriately selected depending on the application, but is usually preferably 10 to 500 μm, more preferably 20 to 300 μm.
[0019] <Resin layer (X)> The resin layer (X) of the present invention must contain CNTs (a) and inorganic particles (b).
[0020] By using such a resin layer (X), a laminated polyester film having the resin layer (X) on at least one side of a polyester film has excellent antistatic properties and also has excellent antistatic properties after carrying out a discharge treatment.
[0021] The resin layer (X) used in the laminated polyester film of the present invention will be described below.
[0022] (1) Resin layer (X) The resin layer (X) of the present invention is required to contain CNTs (a) and inorganic particles (b). It is more preferable that the resin layer (X) satisfies the following formula 1 when the surface resistivity of the resin layer (X) surface is P1 (Ω / □). P1<1.0×10 9 (Formula 1) The method for measuring the surface resistivity of the resin layer (X) surface before and after the corona discharge treatment test will be described later.
[0023] P1 is 1.0×10 9 In the above cases, the antistatic properties are deteriorated, and there is a practical problem when used for protective films or cover tapes for electronic parts that require a high level of antistatic properties. 8 It is preferable that the value is less than 1.0×10 7 It is more preferable that:
[0024] An example of a method for making P1 satisfy formula 1 is to incorporate CNTs (a) into the resin layer (X), preferably a method of forming a resin layer from a coating composition (x) containing CNTs (a) to obtain the resin layer (X).
[0025] Furthermore, it is further preferable that the resin layer (X) of the present invention satisfies the following formula 2 when the surface resistivity of the resin layer (X) surface after subjecting the resin layer (X) surface to a corona discharge treatment under the following conditions is defined as P2 (Ω / □). P2 / P1≦100 (Formula 2) [Corona discharge treatment conditions] Corona discharge treatment was performed under the following conditions: output 100W, discharge gap with ceramic electrode 1mm, electrode movement speed 6m / min, and treatment number 5 times.
[0026] The corona discharge treatment method and the method for measuring the surface resistivity of the resin layer (X) surface before and after the corona discharge treatment test will be described later.
[0027] If P2 / P1 exceeds 100, this indicates that the antistatic properties after discharge treatment such as corona discharge treatment or plasma discharge treatment are deteriorated, and this may cause practical problems when used in applications where surface treatment such as discharge treatment is performed to improve the adhesiveness of the sealant material. In addition, P2 / P1 is preferably 0.1 or more and 100 or less. More preferably, it is 0.1 or more and 50 or less.
[0028] An example of a method for making P2 / P1 satisfy formula 2 is to incorporate CNTs (a) and inorganic particles (b) into the resin layer (X). A preferred example is a method for forming a resin layer from a coating composition (x) containing CNTs (a) and inorganic particles (b) to obtain the resin layer (X).
[0029] (2) CNT (a) In the laminated polyester film of the present invention, the resin layer (X) must contain CNT (a). In the present invention, CNT refers to a seamless tube in which a honeycomb-structured graphene sheet composed only of carbon atoms is rolled into a cylindrical shape. A graphene sheet wound in one layer is called a single-walled CNT, a graphene sheet wound in two layers is called a double-walled CNT, and a graphene sheet wound in three or more layers is called a multi-walled CNT. The CNT (a) used in the present invention is preferably a straight or bent single-walled CNT, a straight or bent double-walled CNT, a straight or bent multi-walled CNT, or a combination of these.
[0030] Note that the honeycomb structure refers to a network structure mainly composed of six-membered rings. However, due to the structure of the CNT, the bent parts of the tube or the closed parts of the cross section may have ring structures other than six-membered rings, such as five-membered rings or seven-membered rings.
[0031] Among the above CNTs, the CNT (a) used in the present invention is preferably a straight or bent single-walled CNT or a straight and / or bent double-walled CNT from the viewpoint of electrical conductivity. Single-walled CNTs and double-walled CNTs are excellent in terms of dispersibility in a solvent, durability, and manufacturing costs. On the other hand, multi-walled CNTs having three or more layers are excellent in dispersibility and manufacturing costs, but may not provide sufficient electrical conductivity.
[0032] In addition, the CNT(a) used in the present invention preferably has a diameter of 1 nm or more. In addition, the diameter of the CNT(a) is preferably 50 nm or less, more preferably 10 nm or less. If the diameter exceeds 50 nm, the CNT will have a multilayer structure of three or more layers, and the conductive path may diverge between the layers, resulting in a decrease in conductivity. In addition, if a CNT with a diameter of more than 50 nm is used to achieve the same conductivity as a CNT with a diameter of 50 nm or less, a large amount of CNT is required, and not only is the transparency of the conductive film extremely impaired, but even if the amount is increased without limit, sufficient conductivity may not be achieved. Furthermore, if the diameter of the CNT exceeds 50 nm, the adhesiveness and abrasion resistance of the conductive layer may be reduced. On the other hand, it is difficult to manufacture CNTs with a diameter of less than 1 nm.
[0033] The aspect ratio of the CNT (a) used in the present invention is preferably 100 or more. The aspect ratio of the CNT is preferably 5000 or less. By setting the aspect ratio of the CNT within the above range, the electrical conductivity of the resin layer (X) can be increased. When the aspect ratio of the CNT is set within the above range, when the in-line coating method described later is used in forming the resin layer (X), the CNT is appropriately loosened in the stretching process, and the conductive path between the CNTs is not broken, and a network with sufficient gaps between the CNTs can be formed. When such a network structure is formed, it is possible to increase the transparency of the film and develop good electrical conductivity properties.
[0034] The aspect ratio is the length (nm) of the carbon tube divided by the diameter (nm) of the carbon tube (length (nm) of the carbon tube / diameter (nm) of the carbon tube).
[0035] CNTs with such characteristics can be obtained by known manufacturing methods such as chemical vapor deposition, catalytic vapor phase growth, arc discharge, and laser evaporation. When producing CNTs, fullerenes, graphite, and amorphous carbon are simultaneously produced as by-products, and catalytic metals such as nickel, iron, cobalt, and yttrium also remain, so it is preferable to remove these impurities and purify the CNTs. To remove impurities, ultrasonic dispersion treatment is effective in addition to acid treatment with nitric acid, sulfuric acid, etc., and separation by a filter is more preferable in terms of improving purity.
[0036] Single-walled CNTs and double-walled CNTs are generally thinner than multi-walled CNTs, and if uniformly dispersed, they can secure a larger number of conductive paths per unit volume, resulting in high conductivity. However, depending on the manufacturing method, a large amount of semiconducting CNTs may be produced as a by-product, and in that case, it becomes necessary to selectively manufacture or select conductive CNTs. Multi-walled CNTs generally exhibit conductivity, but if the number of layers is too large, the number of conductive paths per unit weight decreases. Therefore, even when multi-walled CNTs are used, the CNT diameter is preferably 50 nm or less, more preferably 20 nm or less, and even more preferably 10 nm or less. In addition, when single-walled CNTs or double-walled CNTs are used, due to their structure, it is preferable that the diameter is 20 nm or less, and even more preferably 10 nm or less, from the viewpoint of conductivity.
[0037] The content of CNT (a) in the resin layer (X) used in the present invention is preferably 0.05% by weight or more and 10.0% by weight or less based on the entire resin layer (X). More preferably, it is 0.5% by weight or more and 10% by weight or less, and even more preferably, it is 1.0% by weight or more and 5.0% by weight or less. If it is less than 0.05% by weight, the resin layer (X) does not have sufficient antistatic performance. If it exceeds 10.0% by weight, the cohesive force due to the intermolecular force between the CNTs increases, and the dispersibility of the CNTs decreases, which may deteriorate the transparency of the resin layer (X) and the coating appearance.
[0038] (3) Inorganic particles (b) In the present invention, the resin layer (X) must contain inorganic particles (b) in addition to the CNTs (a). Examples of the inorganic particles (b) used in the present invention include oxide particles containing at least one element selected from the group consisting of Si, Al, Ti, Zr, Se, and Fe.
[0039] Representative examples of the inorganic particles (b) used in the present invention include SiO2, Al2O3, TiO2, and ZrO2.
[0040] When the resin layer (X) of the laminated polyester film of the present invention contains CNTs (a) and inorganic particles (b), the electrical conductivity of the resin layer (X) can be greatly improved (the surface resistivity value can be greatly reduced). It is presumed that the inclusion of inorganic particles (b) in the resin layer (X) reduces the volume of space in which CNTs can exist in the resin (X) layer, thereby improving the density of CNTs and making it easier for CNTs to form a network, which makes it easier to form a conductive path and improves antistatic properties. In addition, as a result of intensive studies by the present inventors, it was surprisingly found that when the resin layer (X) of the laminated polyester film contains CNTs (a) and inorganic particles (b), it is possible to suppress the decrease in antistatic properties even when a discharge treatment is performed. Although it is not clear how this effect is achieved, it is presumed that when a discharge treatment is performed on a resin layer (X) containing CNTs, the CNTs (a) are damaged and the conductive paths of the CNTs (a) are destroyed, whereas when inorganic particles (b) are present, the inorganic particles (b) are densely arranged around the CNTs (a), making the CNTs (a) less susceptible to damage and resulting in excellent antistatic properties even after the discharge treatment.
[0041] The content of the inorganic particles (b) in the resin layer (X) is preferably 5.0% by weight or more based on the entire resin layer (X). More preferably, it is 10.0% by weight or more, and even more preferably, it is 20.0% by weight or more. When the content is set to such a value, the surface resistance value P1 (Ω / □) of the surface of the resin layer (X) is 1.0×10 9 It is preferable because it becomes easy to keep P2 / P1 at or below 100. It is further preferable because it becomes easy to keep P2 / P1 at or below 100. On the other hand, from the viewpoints of transparency and processability, it is preferable that it is at or below 25.0% by weight.
[0042] The inorganic particles (b) used in the laminated polyester film of the present invention are preferably a composition (bc) having an acrylic resin (c) on a part or all of the surface of the inorganic particles (b). The composition (bc) having the acrylic resin (c) is preferable because it is possible to nano-disperse the inorganic particles (b) in the resin layer (X) of the laminated polyester film, and it is highly effective in suppressing damage to the CNT during discharge treatment.
[0043] The method for preparing the composition (bc) having the acrylic resin (c) on a part or the whole of the surface of the inorganic particles (b) is not particularly limited, and examples thereof include a method of surface-treating the inorganic particles (b) with the acrylic resin (c) described below. Specifically, the following methods (i) to (iv) are exemplified. In the present invention, the surface treatment refers to a treatment in which the acrylic resin (c) is adsorbed or adhered to the whole or part of the surface of the inorganic particles (b) having a specific element.
[0044] (i) A method in which a mixture of inorganic particles (b) and acrylic resin (c) is mixed in advance, is added to a solvent, and then dispersed.
[0045] (ii) A method of adding inorganic particles (b) and acrylic resin (c) in that order to a solvent and dispersing them.
[0046] (iii) A method in which inorganic particles (b) and acrylic resin (c) are dispersed in advance in a solvent, and the resulting dispersion is mixed.
[0047] (iv) A method in which inorganic particles (b) are dispersed in a solvent, and then an acrylic resin (c) is added to the resulting dispersion.
[0048] The desired effect can be obtained by any of these methods.
[0049] As the dispersion device, a dissolver, a high-speed mixer, a homomixer, a meader, a ball mill, a roll mill, a sand mill, a paint shaker, an SC mill, an annular mill, a pin mill, etc. can be used.
[0050] As a dispersion method, the above-mentioned device is used to rotate the rotating shaft at a peripheral speed of 5 to 15 m / s for a rotation time of 5 to 10 hours.
[0051] In addition, it is more preferable to use dispersion beads such as glass beads during dispersion in order to improve dispersibility. The diameter of the beads is preferably 0.05 to 0.5 mm, more preferably 0.08 to 0.5 mm, and particularly preferably 0.08 to 0.2 mm.
[0052] The mixing and stirring can be carried out by shaking the container by hand, using a magnetic stirrer or stirring blade, irradiating with ultrasonic waves, or dispersing with vibration.
[0053] The presence or absence of acrylic resin (c) adsorbed or attached to all or part of the surface of inorganic particles (b) can be confirmed by the following analytical method. The measurement object is centrifuged (rotation speed 3,0000 rpm, separation time 30 minutes) using a Hitachi tabletop ultracentrifuge (manufactured by Hitachi Koki Co., Ltd.: CS150NX) to settle the inorganic particles (b) (and the acrylic resin (c) adsorbed to the surface of the inorganic particles (b)), and the supernatant is removed and the sediment is concentrated and dried. The concentrated and dried sediment is analyzed by X-ray photoelectron spectroscopy (XPS) to confirm the presence or absence of acrylic resin (c) on the surface of inorganic particles (b). When it is confirmed that 1% by weight or more of acrylic resin (c) is present on the surface of inorganic particles (b) relative to the total of 100% by weight of inorganic particles (b), it is deemed that acrylic resin (c) is adsorbed or attached to the surface of gold inorganic particles (b).
[0054] (4) Resin (c) In the present invention, it is preferable that the resin layer (X) contains a resin (c) containing at least one resin selected from the group consisting of polyester resin, acrylic resin, urethane resin, and acrylic urethane copolymer resin, from the viewpoints of improving the film-forming properties of the resin layer and maintaining antistatic properties.
[0055] The polyester resin used in the resin layer (X) in the present invention may be, for example, a polyester having the same skeleton as the polyester exemplified as the polyester constituting the polyester film serving as the substrate.
[0056] As a method for obtaining a laminated polyester film having a resin layer (X) containing the CNT (a), inorganic particles (b), and resin (c), for example, a method of applying a coating composition (x) containing the CNT (a), inorganic particles (b), and resin (c) to at least one side of a polyester film and then forming a resin layer (X) can be mentioned. When the resin (c) contains a polyester resin and water is used as a solvent for the coating composition (x), it is preferable that the polyester resin is copolymerized with a compound containing a carboxylate group or a compound containing a sulfonate group in order to improve the adhesiveness of the polyester resin or to facilitate the water solubility of the polyester resin. Examples of compounds containing a carboxylate group include trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, 4-methylcyclohexene-1,2,3-tricarboxylic acid, trimesic acid, 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 5-(2,5-dioxotetrahydrofurfuryl)-3-methyl-3-cyclohexene-1,2-di ... and 5-(2,5-dioxotetrahydrofurfuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid. Examples of the carboxylic acid that can be used include, but are not limited to, (2,3,6,7-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, ethylene glycol bistrimellitate, 2,2',3,3'-diphenyltetracarboxylic acid, thiophene-2,3,4,5-tetracarboxylic acid, ethylenetetracarboxylic acid, and alkali metal salts, alkaline earth metal salts, and ammonium salts thereof.
[0057] Examples of compounds containing a sulfonate group include, but are not limited to, sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfoisophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, sulfo-p-xylylene glycol, 2-sulfo-1,4-bis(hydroxyethoxy)benzene, and alkali metal salts, alkaline earth metal salts, and ammonium salts thereof. Preferred polyester resins include copolymers using terephthalic acid, isophthalic acid, sebacic acid, 5-sodium sulfoisophthalic acid, trimellitic acid, pyromellitic acid, 5-(2,5-dioxotetrahydrofurfuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid as the acid component and ethylene glycol, diethylene glycol, 1,4-butanediol, or neopentyl glycol as the glycol component.
[0058] The acrylic resin used in the present invention refers to a resin obtained by copolymerizing an acrylic monomer described below and, if necessary, other monomers by a known acrylic resin polymerization method such as emulsion polymerization or suspension polymerization.
[0059] Examples of acrylic monomers used in acrylic resins include alkyl acrylates (alkyl groups include methyl, ethyl, n-propyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.), alkyl methacrylates (alkyl groups include methyl, ethyl, n-propyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.), hydroxyl group-containing monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, and 2-hydroxypropyl methacrylate, acrylamide, methacrylamide, N-methyl methacrylamide, N-methyl acrylamide, Examples of such monomers include amide group-containing monomers such as N-methylolacrylamide, N-methylolmethacrylamide, N,N-dimethylolacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N-butoxymethylacrylamide, and N-phenylacrylamide; amino group-containing monomers such as N,N-diethylaminoethyl acrylate and N,N-diethylaminoethyl methacrylate; glycidyl group-containing monomers such as glycidyl acrylate and glycidyl methacrylate; and monomers containing a carboxyl group or a salt thereof, such as acrylic acid, methacrylic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, and the like).
[0060] These acrylic monomers can also be used in combination with other monomers. Examples of the other monomers include glycidyl group-containing monomers such as allyl glycidyl ether, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride, vinyl isocyanate, allyl isocyanate, styrene, vinyl methyl ether, vinyl ethyl ether, vinyl trisalkoxysilane, alkyl maleic acid monoester, alkyl fumaric acid monoester, acrylonitrile, methacrylonitrile, alkyl itaconic acid monoester, vinylidene chloride, vinyl acetate, vinyl chloride, and vinylpyrrolidone.
[0061] One or more acrylic monomers are used for polymerization. When other monomers are used in combination, the proportion of the acrylic monomer in the total monomers is preferably 50% by weight or more, more preferably 70% by weight or more.
[0062] The urethane resin used in the present invention refers to a resin obtained by reacting a polyhydroxy compound with a polyisocyanate compound by a known urethane resin polymerization method such as emulsion polymerization or suspension polymerization.
[0063] Examples of polyhydroxy compounds include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene glycol, hexamethylene glycol, tetramethylene glycol, 1,5-pentanediol, diethylene glycol, triethylene glycol, polycaprolactone, polyhexamethylene adipate, polyhexamethylene sebacate, polytetramethylene adipate, polytetramethylene sebacate, trimethylolpropane, trimethylolethane, pentaerythritol, polycarbonate diol, and glycerin.
[0064] Furthermore, as described above, in the laminated polyester film of the present invention, the inorganic particles (b) are preferably a composition (bc) having an acrylic resin (c) on a part or the whole of the surface thereof. By using the composition (bc) having the acrylic resin (c), the inorganic particles (b) in the laminated polyester film can be nano-dispersed, and the transparency of the laminated polyester film can be maintained.
[0065] The acrylic resin (c) in the present invention is preferably a resin having a monomer unit (c1) represented by formula (1), a monomer unit (c2) represented by formula (2), and a monomer unit (c3) represented by formula (3).
[0066] [ka]
[0067] (In formula (1), R1 group represents a hydrogen atom or a methyl group, and n represents an integer of 9 or more and 34 or less).
[0068] [ka]
[0069] (In formula (2), the R2 group represents a hydrogen atom or a methyl group, and the R4 group represents a group containing two or more saturated carbon rings.)
[0070] [ka]
[0071] (In formula (3), the R3 group represents a hydrogen atom or a methyl group, and the R5 group represents a hydroxyl group, a carboxyl group, a tertiary amino group, a quaternary ammonium salt group, a sulfonic acid group, or a phosphate group.) Here, the acrylic resin (c) in the present invention is preferably a resin having a monomer unit (d1) represented by formula (1).
[0072] In formula (1), when an acrylic resin having a monomer unit with n less than 9 is used, the dispersibility of the inorganic particles (b) in the aqueous solvent (details of the aqueous solvent will be described later) becomes unstable. When an acrylic resin having a monomer unit with n less than 9 in formula (1) is used, the inorganic particles (b) may aggregate violently in the coating composition, and in some cases, the inorganic particles (b) may settle in the aqueous solvent. As a result, the effect of suppressing damage to the CNT during discharge treatment may be lost. On the other hand, an acrylic resin having a monomer unit with n greater than 34 in formula (1) has extremely low solubility in aqueous solvents, so that aggregation of the acrylic resin is likely to occur in the aqueous solvent. Such aggregates are larger than the wavelength of visible light, and therefore, it may not be possible to obtain a laminated polyester film with good transparency. By using a resin having monomer units (c1) represented by the above formula (1), the inorganic particles (b) are dispersed in an aqueous solvent with appropriate interactions, while after drying, the inorganic particles (b) have anisotropy and finely aggregate at the nano-order level in the resin layer (X) of the laminated polyester film, thereby suppressing exposure of the CNTs (a) and improving corona resistance.
[0073] In order for the acrylic resin (c) in the present invention to have the monomer unit (c1) represented by formula (1), it is necessary to use as a raw material the (meth)acrylate monomer (c1') represented by the following formula (4) and polymerize it.
[0074] The (meth)acrylate monomer (c1') is preferably a (meth)acrylate monomer represented by formula (4) in which n is an integer of 9 or more and 34 or less, more preferably a (meth)acrylate monomer in which n is an integer of 11 or more and 32 or less, and even more preferably a (meth)acrylate monomer in which n is an integer of 13 or more and 30 or less.
[0075] [ka]
[0076] The (meth)acrylate monomer (c1') is not particularly limited as long as it is a (meth)acrylate monomer in which n in formula (4) is 9 or more and 34 or less, and specifically includes decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, 1-methyltridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, docosyl (meth)acrylate, tetracosyl (meth)acrylate, triacontyl (meth)acrylate, etc., and dodecyl (meth)acrylate and tridecyl (meth)acrylate are particularly preferred. These may be used alone or in a mixture of two or more.
[0077] It is also important that the acrylic resin (c) in the present invention is a resin having the monomer unit (c2) represented by the above formula (2).
[0078] In the formula (2), if an acrylic resin having a monomer unit containing only one saturated carbon ring is used, the function as a steric hindrance becomes insufficient, and the inorganic particles (b) may aggregate or settle in the coating composition, or in some cases, the inorganic particles (b) may settle in the aqueous solvent. As a result, the transparency of the laminated polyester film may be impaired.
[0079] Such aggregates are larger than the wavelength of visible light, and therefore it may be impossible to obtain a laminated polyester film having good transparency. In order for the acrylic resin (c) in the present invention to have the monomer unit (c2) represented by formula (2), it is necessary to use the (meth)acrylate monomer (c') represented by the following formula (5) as a raw material and polymerize it.
[0080] Examples of the (meth)acrylate monomer (c2') represented by formula (5) include compounds having various cyclic structures such as a bridged condensed cyclic structure (having a structure in which two or more rings are bonded to each other by sharing two elements) and a spirocyclic structure (having a structure in which two cyclic structures are bonded to each other by sharing one carbon element), specifically, a bicyclo, tricyclo, or tetracyclo group, and among these, a (meth)acrylate containing a bicyclo group is particularly preferred from the viewpoint of compatibility with the binder.
[0081] [ka]
[0082] Examples of the (meth)acrylate containing a bicyclo group include isobornyl (meth)acrylate, bornyl (meth)acrylate, disilocyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, adamantyl (meth)acrylate, and dimethyladamantyl (meth)acrylate, with isobornyl (meth)acrylate being particularly preferred.
[0083] Furthermore, the acrylic resin (c) in the present invention is preferably a resin having a monomer unit (c3) represented by the above formula (3).
[0084] When an acrylic resin having a monomer unit in which the R5 group in formula (3) does not have any of a hydroxyl group, a carboxyl group, a tertiary amino group, a quaternary ammonium group, a sulfonic acid group, or a phosphate group is used, the compatibility of the acrylic resin in aqueous solvents becomes insufficient, and the acrylic resin may precipitate in the coating composition, and the inorganic particles (b) may aggregate or settle, or the inorganic particles (b) may aggregate during the drying process.
[0085] Such aggregates are larger than the wavelength of visible light, and therefore it may be impossible to obtain a laminated polyester film having good transparency. In order for the acrylic resin (c) in the present invention to have the monomer unit (c3) represented by formula (3), it is necessary to use the (meth)acrylate monomer (c3') represented by formula (6) as a raw material and polymerize it.
[0086] Examples of the (meth)acrylate monomer (c3') represented by the formula (6) include the following compounds.
[0087] [ka]
[0088] Examples of the (meth)acrylate monomer having a hydroxyl group include monoesters of polyhydric alcohols such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate with (meth)acrylic acid, and compounds obtained by ring-opening polymerization of the monoesters with ε-caprolactone, with 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate being particularly preferred.
[0089] Examples of the (meth)acrylate monomer having a carboxyl group include α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid, and half esters of hydroxyalkyl (meth)acrylates and acid anhydrides, with acrylic acid and methacrylic acid being particularly preferred.
[0090] Examples of the tertiary amino group-containing monomer include N,N-dialkylaminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate; and N,N-dialkylaminoalkyl (meth)acrylamides such as N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylamide, with N,N-dimethylaminoethyl (meth)acrylate being particularly preferred.
[0091] As the quaternary ammonium base-containing monomer, a quaternary ammonium base-containing monomer such as the above-mentioned tertiary amino group-containing monomer is preferably reacted with a quaternizing agent such as epihalohydrin, benzyl halide, or alkyl halide. Specifically, 2-(methacryloyloxy)ethyl trimethyl ammonium chloride, 2-(methacryloyloxy)ethyl trimethyl ammonium bromide, 2-(methacryloyloxy)ethyl trimethyl ammonium dimethyl phosphate and other (meth)acryloyloxy alkyl trialkyl ammonium salts, methacryloyl aminopropyl trimethyl ammonium chloride, methacryloyl aminopropyl trimethyl ammonium bromide and other (meth)acryloyl amino alkyl trialkyl ammonium salts, tetraalkyl (meth)acrylates such as tetrabutyl ammonium (meth)acrylate, trialkyl benzyl ammonium (meth)acrylates such as trimethyl benzyl ammonium (meth)acrylate, and the like, and 2-(methacryloyloxy)ethyl trimethyl ammonium chloride is particularly preferred.
[0092] Examples of sulfonic acid group-containing monomers include (meth)acrylamide-alkanesulfonic acids such as butylacrylamidosulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid, and sulfoalkyl (meth)acrylates such as 2-sulfoethyl (meth)acrylate, with 2-sulfoethyl (meth)acrylate being particularly preferred.
[0093] Examples of the phosphoric acid group-containing acrylic monomer include acid phosphooxyethyl (meth)acrylate, and acid phosphooxyethyl (meth)acrylate is particularly preferred.
[0094] Among these, it is particularly preferred that the acrylic resin (c) is a resin having a monomer unit (c3) represented by the above formula (3), and the R5 group in formula (3) is a hydroxyl group or a carboxyl group, since this has a high adsorption force with the inorganic particles (b) described later and can form a stronger film.
[0095] The acrylic urethane copolymer resin used in the present invention is not particularly limited as long as it is a resin in which an acrylic resin and a urethane resin are copolymerized, but an acrylic urethane copolymer resin having an acrylic resin as a skin layer and a urethane resin as a core layer is particularly preferred because it has excellent adhesion to the laminate laminated on the present laminated polyester film.
[0096] In addition, the laminated polyester film must have a resin layer (X) on at least one side of the polyester film (substrate film) serving as a substrate, but may also have a resin layer (X) on the other side, or may have a resin layer (Y) different from the resin layer (X). The resin constituting the resin layer (Y) is not particularly limited, but examples thereof include polyester resin, acrylic resin, urethane resin, epoxy resin, amide resin, and copolymer resins of these resins. In addition, one or more of these resins may be used. By providing a resin layer on the opposite side to the resin layer (X), for example, by incorporating easy-slip particles into the resin layer on the opposite side to the resin layer (X) of the laminated polyester film of the present invention, the handling property of the film can be further improved, which is preferable.
[0097] (5) Crosslinking agent (d) The laminated polyester film of the present invention may contain a crosslinking agent (d) in addition to the CNT (a), inorganic particles (b), and resin (c) in the resin layer (X). When formed from a coating composition containing the crosslinking agent (d), the resin layer (X) of the laminated polyester film has a dense crosslinked structure, which is preferable because it has excellent stability of antistatic performance. Examples of the crosslinking agent (d) include melamine compounds, oxazoline compounds, carbodiimide compounds, isocyanate compounds, and epoxy compounds.
[0098] As the melamine-based compound, for example, melamine, a methylolated melamine derivative obtained by condensing melamine with formaldehyde, a compound partially or completely etherified by reacting a lower alcohol with methylolated melamine, and a mixture thereof can be used. Specifically, a compound having a triazine and a methylol group is particularly preferable. In the present invention, the melamine compound means a component derived from a melamine compound when the melamine compound described below forms a crosslinked structure with a urethane resin, an acrylic resin, an oxazoline compound, a carbodiimide compound, an isocyanate compound, an epoxy compound, or the like. In addition, the melamine-based compound may be either a monomer or a condensate consisting of a dimer or more polymer, or a mixture thereof. As the lower alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, or the like can be used. The group is an imino group, a methylol group, or an alkoxymethyl group such as a methoxymethyl group or a butoxymethyl group in one molecule, and includes imino group-type methylated melamine resin, methylol group-type methylated melamine resin, methylol group-type methylated melamine resin, and fully alkylated methylated melamine resin. Among them, methylol melamine resin is the most preferable. Furthermore, in order to promote the thermal curing of the melamine compound, an acid catalyst such as p-toluenesulfonic acid may be used.
[0099] When such a melamine-based compound is used, not only does the melamine-based compound self-condense, but the reaction between the hydroxyl groups and carboxyl groups contained in the acrylic resin and the melamine-based compound also progresses, resulting in a stronger layer and a film with excellent antistatic stability.
[0100] The oxazoline compound means an oxazoline compound described below, or a component derived from an oxazoline compound when the oxazoline compound forms a crosslinked structure with a urethane resin, an acrylic resin, a melamine compound, an isocyanate compound, a carbodiimide compound, etc. The oxazoline compound is not particularly limited as long as it has an oxazoline group as a functional group in the compound, but is preferably an oxazoline group-containing copolymer containing at least one monomer containing an oxazoline group and obtained by copolymerizing at least one other monomer.
[0101] As the monomer containing an oxazoline group, 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline, etc. can be used, and one or a mixture of two or more of these can also be used. Among them, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially.
[0102] In the oxazoline compound, the at least one other monomer used for the monomer containing an oxazoline group is not particularly limited as long as it is a monomer that can be copolymerized with the monomer containing an oxazoline group. For example, acrylic acid esters or methacrylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, etc., unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, etc., acrylonitrile, methacrylic acid, etc., and the like can be used. Examples of the monomers that can be used include unsaturated nitriles such as lylonitrile, unsaturated amides such as acrylamide, methacrylamide, N-methylol acrylamide, and N-methylol methacrylamide, vinyl esters such as vinyl acetate and vinyl propionate, vinyl ethers such as methyl vinyl ether and ethyl vinyl ether, olefins such as ethylene and propylene, halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride, and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. These monomers may also be used alone or in mixtures of two or more.
[0103] The carbodiimide compound in the present invention means a carbodiimide compound described below, or a component derived from a carbodiimide compound when the carbodiimide compound forms a crosslinked structure with a urethane resin, an acrylic resin, a melamine compound, an isocyanate compound, an oxazoline compound, etc. The carbodiimide compound is not particularly limited as long as it is a compound having one or more carbodiimide groups or cyanamide groups in a tautomeric relationship therewith as functional groups in the compound.
[0104] A known technique can be applied to the production of a carbodiimide compound, and generally, a carbodiimide compound is obtained by polycondensing a diisocyanate compound in the presence of a catalyst. As the diisocyanate compound, which is the starting material of the carbodiimide compound, aromatic, aliphatic, alicyclic diisocyanates, etc. can be used, and specifically, tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, etc. can be used.
[0105] (6) CNT dispersant (e) In the present invention, the coating composition (x) for forming the resin layer (X) preferably contains a CNT dispersant (e) in addition to the CNTs (a) and inorganic particles (b).
[0106] Examples of the CNT dispersant (e) include water-soluble cellulose and / or water-soluble cellulose derivatives, polystyrene sulfonates, polyvinylpyrrolidone polymers, etc. Among these, water-soluble cellulose and / or water-soluble cellulose derivatives are preferred.
[0107] Representative examples of the polystyrene sulfonate used in the present invention include sodium polystyrene sulfonate and calcium polystyrene sulfonate.
[0108] A representative example of the polyvinylpyrrolidone polymer used in the present invention is polyvinylpyrrolidone.
[0109] Furthermore, a representative example of the water-soluble cellulose derivative used in the present invention is a metal salt of carboxycellulose. Here, carboxycellulose is cellulose in which the hydroxyl group of the glucopyranose monomer constituting the cellulose skeleton is replaced with a carboxyl group (when the glucopyranose monomer has a plurality of hydroxyl groups, at least one of the hydroxyl groups may be replaced with a carboxyl group). Here, the term "carboxyl group" refers not only to a carboxyl group in the narrow sense, but also to a carboxyalkyl group. By using a metal salt of carboxycellulose, the water solubility can be dramatically increased, and the CNT dispersibility can be improved. Among the metal salts of carboxycellulose, metal salts of carboxyalkylcellulose are preferred because of their good water solubility, and metal salts of carboxymethylcellulose, which are inexpensive and widely used industrially, are more preferred, and among these, sodium carboxymethylcellulose and calcium carboxymethylcellulose are preferred. Sodium carboxymethylcellulose is particularly preferred.
[0110] By including the above-mentioned CNT dispersant (e) in the coating composition (x), the CNTs are easily dissolved in water, and furthermore, the CNT dispersant (e) is uniformly dispersed in the vicinity of the CNTs in the solvent, suppressing aggregation due to the affinity between CNTs. In other words, a coating composition containing stable and finely dispersed CNTs can be produced.
[0111] In the present invention, the CNT dispersant (e) is preferably 0.1% by weight or more and 15% by weight or less based on the solid content weight in the coating composition (x). More preferably, it is 0.1% by weight or more and 7.5% by weight. By making the content of the CNT dispersant (e) 0.1% by weight or more, the CNTs (a) in the coating composition (x) and the resin layer (X) can be uniformly dispersed, which is preferable in terms of transparency and antistatic properties.
[0112] In the present invention, the ratio of the content of CNT (a) and CNT dispersant (e) in the coating composition (x), (e) / (a), is preferably 0.5 or more and 15 or less. More preferably, it is 0.5 or more and 5 or less. By making (e) / (a) 0.5 or more, the coating composition (x) can be stably prepared without causing aggregation of CNTs even when mixed with the resin (c) and the crosslinking agent (d). In addition, when (e) / (a) exceeds 15.0, the amount of CNT dispersant (e) becomes excessive relative to CNT (a), and the antistatic properties of the resin layer (X) may be deteriorated.
[0113] (7) Paint composition (x) The laminated polyester film of the present invention can be produced, for example, by laminating a resin layer (X) onto a polyester film using a coating composition (x) containing CNTs (a), inorganic particles (b), and, if necessary, the aforementioned resin (c), crosslinking agent (d), and CNT dispersant (e).
[0114] The coating composition (x) containing CNT (a) and inorganic particles (b) may contain a small amount of water-soluble organic solvent from the viewpoint of improving the storage stability and handling of the coating agent. Examples of the water-soluble organic solvent include water-soluble alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol, water-soluble ketones such as acetone, and water-soluble ethers such as methyl cellosolve, cellosolve, butyl cellosolve, carbitol, and butyl carbitol. These can be used alone or in combination. The content of the water-soluble organic solvent is preferably 10% by weight or less, more preferably 7% by weight or less, and even more preferably 5% by weight or less, based on the total amount of the coating composition (x) from the viewpoint of explosion-proofness and environmental pollution.
[0115] A method for obtaining a laminated polyester film having a resin layer (X) formed from a coating composition (x) containing CNTs (a) and inorganic particles (b) includes a method for laminating a resin layer (X) on a polyester film. Among them, a method for coating (applying) a coating composition (x) constituting the resin layer (X) on a polyester film and laminating the polyester film is preferable. Coating methods for the coating agent include a method for coating in a separate process from the polyester film manufacturing process, that is, a so-called offline coating method, and a so-called in-line coating method for coating during the polyester film manufacturing process to obtain a laminated polyester film in which the resin layer (X) is laminated on the polyester film at once. However, it is preferable to adopt the in-line coating method from the viewpoint of cost and uniformity of the coating thickness, and the solvent of the coating liquid used in this case is preferably water-based from the viewpoint of environmental pollution and explosion resistance, and the most preferable embodiment is to use water.
[0116] For example, a polyester film before crystal orientation that has been melt-extruded is stretched in the longitudinal direction by about 2.5 to 5 times, and the coating composition (x) that constitutes the resin layer (X) is continuously applied to the uniaxially stretched film. The coated film is dried while passing through a stepwise heated zone, and is stretched by about 2.5 to 5 times in the width direction. It can be obtained by a method (in-line coating method) in which the film is continuously led to a heating zone at 150 to 250°C to complete the crystal orientation.
[0117] In the present invention, the crosslinking reaction between the resin (c) and the crosslinking agent (d) is promoted by the high-temperature heat treatment in the heating zone, and the stability of the antistatic performance of the resin layer (X) is improved. Therefore, it is preferable to adopt the in-line coating method in terms of performance as well.
[0118] Examples of methods that can be used to apply a coating composition using water as a solvent (water-based coating agent) include reverse coating, spray coating, bar coating, gravure coating, rod coating, and die coating.
[0119] It is preferable to subject the surface of the polyester film substrate to a corona discharge treatment or the like before applying the coating composition (x), because this improves the adhesion between the polyester film and the resin layer (X) and improves the coatability.
[0120] In the resin layer (X), a crosslinking agent, an antioxidant, a heat stabilizer, a weather stabilizer, an ultraviolet absorber, an organic lubricant, a pigment, a dye, organic or inorganic fine particles, a filler, a surfactant, and the like may be blended within the range not impairing the effects of the invention.
[0121] (8) Laminated polyester film The laminated polyester film of the present invention preferably has a haze of 3.0% or less, since this improves visibility when various inspections are carried out through the laminated polyester film, and more preferably has a haze of 2.5% or less.
[0122] <Method of manufacturing laminated polyester film> Next, a method for producing a laminated polyester film will be described. First, a polyethylene terephthalate (hereinafter, abbreviated as PET) film will be used as the polyester film, but the method is not limited thereto. First, PET pellets are thoroughly vacuum-dried, then fed into an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to produce an unstretched (unoriented) PET film (film A). This film is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film (film B). The coating composition of the present invention, which has been prepared to a predetermined concentration, is applied to one side of this film B. At this time, the coating surface of the PET film may be subjected to a surface treatment such as a corona discharge treatment before coating. By performing a surface treatment such as a corona discharge treatment, the wettability of the coating composition to the PET film can be improved, the coating composition can be prevented from being repelled, and a uniform coating thickness can be achieved.
[0123] After coating, the PET film is held at the edge with clips and guided to a heat treatment zone (preheating zone) at 80-130°C to dry out the solvent in the coating composition. After drying, the film is stretched 1.1-5.0 times in the width direction. It is then guided to a heat treatment zone (thermal setting zone) at 160-240°C and heat-treated for 1-30 seconds to complete the crystal orientation.
[0124] In this heat treatment step (thermal fixation step), a relaxation treatment of 3 to 15% may be performed in the width direction or the length direction as necessary. In addition, particles may be added to the polyester film raw material in order to impart functions such as runnability (slipperiness), weather resistance, and heat resistance to the laminated polyester film, within a range that does not impair the effects of the invention. As the material of the particles to be added to the polyester film raw material, additives such as heat stabilizers, oxidation stabilizers, weather resistance stabilizers, ultraviolet absorbers, and slip agents can be used. In addition, the coating agent used in this case is preferably a water-based coating agent in terms of environmental pollution and explosion resistance.
[0125] [Methods of measuring characteristics and evaluating effects] (1) Transparency measurement method Transparency was evaluated by haze (%). The haze was measured by leaving the laminated polyester film for 1 hour under normal conditions (temperature 23°C, relative humidity 65%) and then using a turbidity meter "NDH5000" manufactured by Nippon Denshoku Industries Co., Ltd. The average value of three measurements was regarded as the haze of the laminated polyester film.
[0126] (2) Appearance of coating The appearance of the coating was evaluated by placing the laminated polyester film 30 cm directly under a three-wavelength fluorescent lamp (Panasonic Corporation, three-wavelength daylight white (F·L 15EX-N 15W)) and visually observing it while changing the viewing angle. Grades A and above were considered good, and B was considered to be satisfactory for practical use.
[0127] S: No agglomerates or uneven coating are observed A: Slight agglomerations and uneven coating are visible.
[0128] B: Aggregates and uneven coating are visible.
[0129] C: Aggregates and uneven coating are noticeable.
[0130] (3) Measurement and evaluation methods for antistatic properties (surface resistivity) The antistatic property was evaluated by surface resistivity. The measurement surface was the resin layer (X) surface of the laminated polyester film. The unit is Ω / □.
[0131] (3-1) Method for evaluating the surface resistivity P1 of the resin layer (X) surface before the corona discharge treatment test The laminated polyester film was left for 24 hours under normal conditions (temperature 23°C, relative humidity 65%), and then the surface resistivity was measured in that atmosphere after applying a voltage of 100V for 10 seconds using a digital ultra-high resistance / micro ammeter (Advantest Corporation, R8340A). The measured value was taken as the surface resistivity P1 (Ω / □) of the resin layer (X) surface before the moist heat treatment test. If the surface resistivity was 9×10 11 A value of 5×10 Ω / □ or less indicates that the antistatic properties are at a level that does not pose a problem in practical use. 10 A value of Ω / □ or less indicates excellent antistatic properties.
[0132] (3-2) Method for evaluating the surface resistivity P2 of the resin layer (X) surface after the corona discharge treatment test The laminated polyester film was cut into a size of 10 cm x 20 cm. Next, using a corona surface modification evaluation device TEC-4AX manufactured by Kasuga Electric Co., Ltd., the laminated polyester film was placed on an earth plate with the resin layer (X) facing upward, and a corona discharge treatment was performed under the conditions of a corona discharge treatment output of 100 W, a discharge gap with the ceramic electrode of 1 mm, an electrode moving speed of 6 m / min, and 5 treatments. The surface resistivity of the laminated polyester film sample that had been subjected to the corona discharge treatment was determined in the same manner as in (3-1). The measured value was taken as the surface resistivity P2 (Ω / □) of the resin layer (X) surface after the moist heat treatment test. If the surface resistivity was 9×10 11 A value of 5×10 Ω / □ or less indicates that the antistatic properties are at a level that does not pose a problem in practical use. 10 A value of Ω / □ or less indicates excellent antistatic properties.
[0133] (4) Method for Analyzing Inorganic Particle Species Contained in Resin Layer (X) (4-1) Presence or absence of inorganic particles in the resin layer (X) The surface of the resin layer (X) was observed at 100,000 times magnification using a SEM (scanning electron microscope), and elemental analysis was performed using EDX (energy dispersive X-ray spectroscopy) to determine whether or not inorganic particles were contained.
[0134] Specifically, the surface morphology observed with a Hitachi High-Technologies field emission scanning electron microscope (model number S-4800) was subjected to element detection measurement with a Bruker AXS QUANTAX Flat QUAD System (model number Xflash 5060FQ) to confirm the presence or absence of oxide particles containing at least one element selected from the group consisting of Si, Al, Ti, Zr, Se, and Fe.
[0135] (4-2) Content of inorganic particles in resin layer (X) The content of inorganic particles in the cross section of the resin molded body was measured by observing the cross section using a transmission electron microscope (TEM) according to the following method. First, an ultra-thin section of the cross section of the resin layer (X) was photographed with a TEM at a magnification of 100,000 times. Next, the image was converted to grayscale using the image processing software EasyAccess Ver6.7.1.23, the white balance was adjusted so that the brightest and darkest parts were within an 8-bit tone curve, and the contrast was adjusted so that the boundaries of the individual filler components were clearly distinguishable. Next, using software (image processing software ImageJ / developer: National Institutes of Health (NIH)), the pixels were binarized at the aforementioned boundaries, and the areas of the individual inorganic particles were extracted using the Analyze Particles function, and the total occupied area rate of the corresponding areas was calculated to obtain the volume filling rate. EXAMPLES
[0136] Next, the present invention will be described based on examples, but the present invention is not limited to these. In addition, Examples 1 to 3, 7, 8, 14, 15, 18 to 20, 24, 25, 30 and 34 shall be read as Reference Examples 1 to 3, 7, 8, 14, 15, 18 to 20, 24, 25, 30 and 34.In addition, a method for synthesizing a CNT aqueous dispersion (ae) containing CNT (a) and a CNT dispersant (e), and a method for synthesizing an aqueous dispersion of an acrylic resin (c) and an aqueous solution of a polyester resin (c-2) are shown as reference examples.
[0137] (Reference Example 1) Preparation of CNT water dispersion (ae-1) containing CNT (a) and CNT dispersant (e) A CNT aqueous dispersion was prepared by placing 1.0 mg of straight double-walled CNT (manufactured by Science Laboratory, diameter 5 nm, aspect ratio 3000):a-1 as the CNT, 3.0 mg of CNT dispersant (e) sodium carboxymethylcellulose (Sigma-Aldrich Japan, Ltd.) (hereinafter abbreviated as CMC-Na) and 666 mg of water in a sample tube, and irradiating the dispersion with ultrasonic waves for 30 minutes using an ultrasonic crusher (Tokyo Rikakiki Co., Ltd. VCX-502, output 250 W, direct irradiation) to obtain a CNT aqueous dispersion (ae-1) consisting of uniform CNT (a-1) and CNT dispersant (e) (CNT (a-1) concentration 0.15 wt%, CNT dispersant (e) 0.45 wt%, CNT dispersant (e) / CNT (a-1) = 3.0).
[0138] (Reference Example 2) Preparation of CNT water dispersion (ae-2) consisting of CNT (a) and CNT dispersant As the CNT, 1.0 mg of single-walled CNT (manufactured by Science Laboratory, diameter 1.1 nm, aspect ratio 5000):a-2, 3.0 mg of sodium carboxymethylcellulose (Sigma-Aldrich Japan, hereinafter abbreviated as CMC-Na) as the CNT dispersion (e), and 666 mg of water were placed in a sample tube to prepare a CNT aqueous dispersion, which was then irradiated with ultrasonic waves for 30 minutes using an ultrasonic crusher (Tokyo Rikakiki VCX-502, output 250 W, direct irradiation) to obtain a CNT aqueous dispersion (ae-2) consisting of uniform CNT (a-2) and CNT dispersion (e) (CNT (a-2) concentration 0.15 wt%, CNT dispersion (e) 0.45 wt%, CNT dispersion (e) / CNT (a) = 3.0).
[0139] (Reference example 3) An emulsion (EM-1) containing a composition (bc) having an acrylic resin (c) on the surface of inorganic particles (b) A typical acrylic resin reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser was charged with 100 parts by weight of isopropyl alcohol as a solvent, and the mixture was heated and stirred while being maintained at 100°C. Into this, a mixture consisting of 40 parts by weight of eicosyl methacrylate with n=19 as (meth)acrylate (c'-1), 40 parts by weight of isobornyl methacrylate having two rings as (meth)acrylate (c'-2), and 20 parts by weight of 2-hydroxyethyl acrylate as (meth)acrylate having other hydroxyl groups (c'-3) was dropped over 3 hours. After the dropwise addition was completed, the mixture was heated at 100°C for 1 hour, and then an additional catalyst mixture consisting of 1 part by weight of t-butylperoxy 2-ethylhexaate was added. Next, the mixture was heated at 100°C for 3 hours and then cooled to obtain acrylic resin (c-1).
[0140] Inorganic particles (b) containing aluminum element ("NanoTek" Al2O3 slurry (manufactured by C.I. Chemical Co., Ltd., number average particle diameter 60 nm: b-1) were used, and the "NanoTek" Al2O3 slurry and the above acrylic resin (c-1) were added in that order to an aqueous solvent, and dispersed by the following method to obtain an emulsion (EM-1) containing a mixed composition (bc) of inorganic particles (b-1) and acrylic resin (c-1) (method (ii) above). The ratio (weight ratio) of the amounts of inorganic particles (b-1) and acrylic resin (c-1) added was (b-1) / (c-1) = 50 / 50 (the weight ratio was rounded off to the nearest whole number). The dispersion process was carried out using a homomixer and rotating the mixture at a peripheral speed of 10 m / s for 5 hours. The weight ratio of particles (b-1) and acrylic resin (c-1) in the final composition (bc) was (b-1) / (c-1) = 40 / 60 (the weight ratio was rounded off to the nearest whole number).
[0141] The obtained composition (bc) was centrifuged (rotation speed 3000 rpm, separation time 30 minutes) using a Hitachi tabletop ultracentrifuge (manufactured by Hitachi Koki Co., Ltd.: CS150NX) to precipitate the inorganic particles (b) (and the acrylic resin (c) adsorbed on the surfaces of the inorganic particles (b)). The supernatant was then removed and the precipitate was concentrated and dried. The concentrated and dried precipitate was analyzed by X-ray photoelectron spectroscopy (XPS), confirming the presence of acrylic resin (c) on the surfaces of the inorganic particles (b). In other words, it was found that the acrylic resin (c) was adsorbed and attached to the surfaces of the inorganic particles (b), and the obtained composition (bc) corresponded to particles having acrylic resin (c) on the surfaces of the inorganic particles (b).
[0142] (Reference example 4) Emulsion (EM-2) containing composition (bc) having acrylic resin (c) on the surface of inorganic particles (b) EM-2 was obtained in the same manner as in Reference Example 3, except that a Si-containing "Snowtex (registered trademark)" colloidal silica slurry (manufactured by Nissan Chemical Industries, Ltd., number average particle diameter 80 nm): b-2 was used as the inorganic particles (a).
[0143] (Reference example 5) Emulsion (EM-3) containing composition (bc) having acrylic resin (c) on the surface of inorganic particles (b) EM-3 was obtained in the same manner as in Reference Example 3, except that "Nanouse (registered trademark)" ZR (manufactured by Nissan Chemical Industries, Ltd., number average particle diameter 90 nm): b-3 containing Zr element was used as the inorganic particles (b).
[0144] (Reference example 6) Emulsion (EM-4) containing composition (bc) having acrylic resin (c) on the surface of inorganic particles (b) EM-4 was obtained in the same manner as in Reference Example 3, except that the inorganic particles (b) used were “NanoTek” TiO2 slurry (manufactured by CI Chemical Co., Ltd., number average particle diameter 36 nm): b-4 containing Ti element.
[0145] (Reference example 7) Polyester resin (c-2) 50 parts by mass of terephthalic acid, 50 parts by mass of isophthalic acid, 50 parts by mass of ethylene glycol, and 30 parts by mass of neopentyl glycol were charged into a nitrogen-purged reactor together with 0.3 parts by mass of antimony trioxide and 0.3 parts by mass of zinc acetate as polymerization catalysts, and a polymerization reaction was carried out at 190 to 220 ° C. under normal pressure for 12 hours while removing water, to obtain polyester glycol. Next, 5 parts by mass of 5-sodium sulfoisophthalic acid and xylene as a solvent were charged into the reactor to the obtained polyester glycol, and polymerization was carried out for 3 hours while distilling off xylene at 260 ° C. under a reduced pressure of 0.2 mmHg, to obtain a polyester resin (c-2) having hydrophilic functional groups. This polyester resin (c-2) was dissolved in an aqueous solvent containing ammonia water and butyl cellulose to obtain an aqueous solution.
[0146] Example 1 ·Paint composition: The CNT aqueous dispersion (ae-1), emulsion (EM-1), acrylic resin (c-1), and melamine compound (d) were mixed in a solid mass ratio of (ae-1) / (EM-1) / (c) / (d) = 2 / 2.5 / 95 / 2 (CNT (a-1) / inorganic particles (b-1) / acrylic resin (c-1) / melamine compound (d) = 0.5 / 1 / 96.5 / 2). Furthermore, in order to improve the coatability onto polyester film, a fluorosurfactant ("Pluscoat" RY-2 manufactured by GOO Chemical Industry Co., Ltd.) was added in an amount of 0.1 part by mass per 100 parts by mass of the total mixed coating composition described above.
[0147] Melamine compound (d): "Nicalac" (registered trademark) MW-035 (solid content concentration 70% by mass, solvent: water), manufactured by Sanwa Chemical Co., Ltd. Polyester film: PET pellets (intrinsic viscosity 0.64 dl / g) containing 4% by mass of silica particles with a primary particle size of 0.3 μm were thoroughly vacuum-dried, fed to an extruder, melted at about 280°C, extruded into a sheet, and cooled and solidified by wrapping the sheet around a mirror-finished casting drum with a surface temperature of 25°C using an electrostatic casting method. This unstretched film was heated to 90°C and stretched 3.1 times in the longitudinal direction to produce a uniaxially stretched film (film B).
[0148] Laminated film After subjecting the uniaxially stretched film to a corona discharge treatment in air, the coating composition shown in Table 1 was applied to a coating thickness of about 6 μm using a wire bar coater. Then, both ends in the width direction of the uniaxially stretched film to which the coating composition was applied were held with clips and introduced into a preheating zone. The atmospheric temperature in the preheating zone was set to 90 to 100 ° C, and the solvent of the coating composition was dried. Then, the film was continuously stretched 3.6 times in the width direction in a 100 ° C stretching zone, and then heat-treated for 20 seconds in a 240 ° C heat treatment zone to form a resin layer, and further subjected to a 5% relaxation treatment in the width direction at the same temperature to obtain a laminated film in which the crystal orientation of the polyester film was completed. In the obtained laminated film, the thickness of the PET film was 50 μm and the thickness of the resin layer was 70 nm.
[0149] The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity and the change in surface resistivity P2 / P1 were excellent, and the transparency was also good.
[0150] (Examples 2 to 17) A laminated film was obtained in the same manner as in Example 1, except that the solid mass ratios of CNT (a-1), inorganic particles (b-1), resin (c), and crosslinking agent (d) were changed as shown in Table 1. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0151] (Example 18) A laminated film was obtained in the same manner as in Example 7, except that (EM-2) (inorganic particles (b-2) were used as the inorganic particles (b)) was used as the emulsion. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0152] (Examples 19 to 23) A laminate film was obtained in the same manner as in Examples 8 to 12, except that the solid mass ratios of CNT (a-1), inorganic particles (b-2), resin (c), and crosslinking agent (d) were changed as shown in Table 1. The properties of the obtained laminate film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0153] Example 24 A laminated film was obtained in the same manner as in Example 7, except that (EM-3) (inorganic particles (b-3) were used as the inorganic particles (b)) was used as the emulsion. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0154] (Examples 25 to 29) A laminate film was obtained in the same manner as in Examples 8 to 12, except that the solid mass ratios of CNT (a-1), inorganic particles (b-3), resin (c), and crosslinking agent (d) were changed as shown in Table 1. The properties of the obtained laminate film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0155] (Example 30) A laminated film was obtained in the same manner as in Example 9, except that (EM-4) (inorganic particles (b-4) were used as the inorganic particles (b)) was used as the emulsion. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0156] (Examples 31 and 32) A laminate film was obtained in the same manner as in Examples 10 and 11, except that the solid mass ratios of CNT (a-1), inorganic particles (b-4), resin (c), and crosslinking agent (d) were changed as shown in Table 1. The properties of the obtained laminate film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0157] (Example 33) A laminated film was obtained in the same manner as in Example 10, except that the CNT aqueous dispersion (ae-2) was used instead of the CNT aqueous dispersion (ae). The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0158] (Example 34) A laminated film was obtained in the same manner as in Example 7, except that the CNT aqueous dispersion (ae-1), inorganic particles (b-1), acrylic resin (c), and melamine compound (d) were mixed in a solid content ratio of (ae-1) / (b-1) / (c) / (d)=4 / 1 / 96 / 2). The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0159] Example 35 The CNT water dispersion (ae-1), emulsion (EM-1), polyester resin (c-2), and melamine compound (d) were mixed so that the solid mass ratio was (ae-1) / (EM-1) / (c-2) / (d)=4 / 25 / 50 / 24 (CNT (a-1) / inorganic particles (b-1) / acrylic resin (c-1) / polyester resin (c-2) / melamine compound (d)=1 / 10 / 15 / 50 / 24). Furthermore, in order to improve the coatability to the polyester film, a fluorine-based surfactant (GOO Chemical Industry Co., Ltd. "Plus Coat" RY-2) was added so that it was 0.1 parts by mass per 100 parts by mass of the total mixed coating composition. Thereafter, a laminated film was obtained in the same manner as in Example 1. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0160] (Example 36) A laminated film was obtained in the same manner as in Example 35, except that the crosslinking agent (d) was changed from the melamine compound (d) to the oxazoline compound (d-2). The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0161] Oxazoline compound (d-2): "Epocross" (registered trademark) WS-700 (solid content concentration 25% by mass, solvent: water) manufactured by Nippon Shokubai Co., Ltd. (Example 37) A laminated film was obtained in the same manner as in Example 35, except that the crosslinking agent (d) was changed from the melamine compound (d) to a carbodiimide compound (d-3). The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0162] Carbodiimide compound (d-3): "Carbodilite" (registered trademark) V02-L2 (solid content concentration 40 mass%, solvent: water) manufactured by Nisshinbo Chemical Co., Ltd. (Example 38) A laminated film was obtained in the same manner as in Example 35, except that the crosslinking agent (d) was changed so that the solid content mass ratio was melamine compound (d) / oxazoline compound (d-2)=12 / 12. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0163] (Example 39) A laminated film was obtained in the same manner as in Example 35, except that the crosslinking agent (d) was changed so that the solid content mass ratio was oxazoline compound (d-2) / carbodiimide compound (d-3) = 12 / 12. The properties of the obtained laminated film are shown in Table 1. The initial surface resistivity, the change in surface resistivity P2 / P1, and the transparency were all good.
[0164] Comparative Example 1 A laminated film was obtained in the same manner as in Example 7, except that inorganic particles (b) were not used. The properties of the obtained laminated polyester film are shown in Table 1. Since inorganic particles (b) were not used, the change in surface resistivity P2 / P1 was poor.
[0165] Comparative Example 2 A laminated film was obtained in the same manner as in Example 10, except that the inorganic particles (b) and the resin (c) were changed so that the solid content mass ratio was (b) / (c)=10 / 90. The properties of the obtained laminated film are shown in Table 1. Since CNT (a) was not used, the initial surface resistivity was poor.
[0166] [Table 1] [Industrial Applicability]
[0167] The laminated polyester film of the present invention has excellent antistatic properties and can maintain the excellent antistatic properties even after discharge treatment, and therefore can be suitably used in applications where discharge treatment is performed.
Claims
1. A laminated polyester film having a resin layer (X) on at least one side of a polyester film, the resin layer (X) containing single-layered or double-layered carbon nanotubes (a) having a diameter of 50 nm or less and inorganic particles (b), the laminated polyester film satisfying the following formulas 1 and 2, when the surface resistivity of the resin layer (X) surface is P1 (Ω / □) and the surface resistivity of the resin layer (X) surface after subjecting the resin layer (X) surface to a corona discharge treatment under the following conditions is P2 (Ω / □). P1<1.0×10 8 (Formula 1) P2 / P1≦50 (Formula 2) [Corona discharge treatment conditions] Corona discharge treatment was carried out under the conditions of output 100 W, discharge gap with the ceramic electrode 1 mm, electrode movement speed 6 m / min, and treatment number 5 times.
2. 2. The laminated polyester film according to claim 1, wherein the inorganic particles (b) are oxide particles containing at least one element selected from the group consisting of Si, Al, Ti, Zr, Se, and Fe.
3. 3. The laminated polyester film according to claim 1, wherein the content of the carbon nanotubes (a) in the resin layer (X) is 0.05% by weight or more and 5.0% by weight or less based on the entire resin layer (X).
4. 4. The laminated polyester film according to claim 1, wherein the content of the inorganic particles (b) in the resin layer (X) is 5.0% by weight or more based on the total weight of the resin layer (X).
5. The laminated polyester film according to any one of claims 1 to 4, which is used for applications in which a discharge treatment is performed.
6. A method for producing a laminated polyester film according to any one of claims 1 to 5, comprising the steps of applying a coating composition (x) containing carbon nanotubes (a) and inorganic particles (b) to at least one surface of a polyester film before completion of crystal orientation, and then stretching the polyester film by a uniaxial or biaxial stretching method to complete the crystal orientation of the polyester film.
Citation Information
Patent Citations
Biaxially oriented polyester film
JP1986204240A
Laminated film and manufacturing process thereof
JP2004058648A
Composition containing carbon nanotube, composite material having coating film made thereof and method for producing the same
JP2005336341A
Transparent electrode of carbon nanotube pattern containing net-like thin film of carbon nanotube, and its manufacturing method
JP2008177165A
Composition containing carbon nanotube, complex with coating film comprising the same, and its manufacturing method
JP2009155570A